Kara śmierci za przestępstwa dewizowe w totalitarnym systemie komunistycznej Polski Ludowej - Sawicki, Janusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The subject of the article is the penalisation of foreign exchange crimes in the Act of October 28, 1950 on the prohibition of possessing foreign currencies, gold coins, gold, and platinum, as well as the tightening of penalties for certain foreign exchange offenses. In this act, illegal foreign exchange trading was threatened with the most severe penalties, including the death penalty. The article contains a historical outline of liability for foreign exchange crime, from the legal regulations in the Second Polish Republic to the Fiscal Penal Code in force. The author pays special attention to the Act of 1950, which is a symbol of criminal law during the period of Stalinist repressions in Polish People’s Republic. The author introduces the atmosphere of those years, related to the currency reform and radical tightening of criminal liability for foreign exchange offenses, in particular for the illegal trade in foreign currencies. The article indicates the axiological foundations of applying penal repression in the economic area of the state, typical for the totalitarian system of the communist Polish People’s Republic.
Keywords: Polska Ludowa; przestępczość dewizowa; kara śmierci; represje stalinowskie; totalitaryzm